(untitled) (Research, Society and Development, 2020)
Palliative care aims to reaffirm the importance of life, facing death as a natural process, with the family having an important role in this process. The present study aims to know what the national literature has presented, in the period from 2013 to 2019, on the theme of work overload and its dimensions in family care for elderly people in palliative care. This is a reflective study carried out with the support of ten articles and a dissertation selected from the descriptors "caregivers", "elderly" and "home care" in the online research bases Scientific Electronic Electronic Library Online, Latin American and Caribbean Literature in Health Sciences, Nursing Database, International Literature in Health Sciences and Medline. Needs and difficulties are common among family members’ experiences. Caregiver work overload is a multidimensional phenomenon that involves changes both in the individual’s physical and emotional state. The routine of a caregiver requires conditions of emotional, psychological and physical preparation, which often does not happen in all families. Thinking about the reflection on the Palliative Care proposal, it is essential to consider the family as a care unit, the context of family caregivers, it is surrounded by changes and challenges, both in terms of the overload difficulties in caring for the elderly, whether in the absence of socioeconomic conditions.